If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = 10x + -3 Reorder the terms: 10 + -2x = -3 + 10x Solving 10 + -2x = -3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 10 + -2x + -10x = -3 + 10x + -10x Combine like terms: -2x + -10x = -12x 10 + -12x = -3 + 10x + -10x Combine like terms: 10x + -10x = 0 10 + -12x = -3 + 0 10 + -12x = -3 Add '-10' to each side of the equation. 10 + -10 + -12x = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -12x = -3 + -10 -12x = -3 + -10 Combine like terms: -3 + -10 = -13 -12x = -13 Divide each side by '-12'. x = 1.083333333 Simplifying x = 1.083333333
| 4(4/3)-y=5 | | 3*x^2-25=0 | | 2x+1=1024 | | 6+31t-16t^2=4 | | 18a-2a^2=0 | | (-x)*(-x)-3x+10=0 | | 3(4-4)=-6 | | x^3/4=5.2 | | 2y+3=5x+6 | | 2x+3=5y+6 | | -16t^2+64t+80=x | | 2x+2(-4x+4)=13 | | -2=-16t^2+31t+6 | | 17=-2x^3+3x | | xy-34=21 | | x=-4y-2 | | 64x^2+6=10 | | 5x=-2x+27 | | 4.4+1.5x=2.5x | | 6/8×2/7 | | 0=-16t^2+31t+4 | | 7x-15=8x+3 | | 6=-16t^2+31t+4 | | 0=-16t^2+31t+6 | | 8x-24=-6x | | 4=-16t^2+31t+6 | | ex=14 | | -9m^2+4m+8=0 | | (3*sinx)/2=0 | | 3sinx/2=0 | | 7x^2y+14x^2= | | -x+27x+28=0 |